2019
DOI: 10.3390/molecules24040716
|View full text |Cite
|
Sign up to set email alerts
|

Position-Selective Synthesis and Biological Evaluation of Four Isomeric A-Ring Amino Derivatives of the Alkaloid Luotonin A

Abstract: Following two orthogonal synthetic routes, a series of all four possible A-ring amino derivatives of the natural product Luotonin A (a known Topoisomerase I inhibitor) was synthesized. In both strategies, intramolecular cycloaddition reactions are the key step. The target compounds were obtained in good yields by mild catalytic transfer hydrogenation of the corresponding nitro precursors. In-vitro evaluation of the antiproliferative activity towards human tumor cell lines revealed the 4-amino compound (5b) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We previously made positive experiences with the selective reduction of a nitrocarbazolediester by catalytic transfer hydrogenation [14], employing Deady's protocol [15]. Recently, we successfully employed this technique also to the synthesis of A-ring amino derivatives of Luotonin A [4]. In this work, we have applied analogous conditions (hydrazine hydrate as hydrogen source, Pd/C as catalyst, alcoholic solution/suspension at reflux temperature) in an attempt to reduce the NO 2 group in 9-nitro-Luotonin A (1) while leaving ring B intact.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously made positive experiences with the selective reduction of a nitrocarbazolediester by catalytic transfer hydrogenation [14], employing Deady's protocol [15]. Recently, we successfully employed this technique also to the synthesis of A-ring amino derivatives of Luotonin A [4]. In this work, we have applied analogous conditions (hydrazine hydrate as hydrogen source, Pd/C as catalyst, alcoholic solution/suspension at reflux temperature) in an attempt to reduce the NO 2 group in 9-nitro-Luotonin A (1) while leaving ring B intact.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various known Luotonin A derivatives, bearing substituents mainly at ring A or at ring E, there have been only a few examples with a primary amino group at these locations. Our group has recently published the synthesis of four isomeric A-ring amino derivatives [4], and previously two E-ring amino derivatives had been reported: the 7-amino compound was described by Nacro et al [5] and the 8-amino derivative was reported by Cagir et al [6]. In 2004, Dallavalle et al published the synthesis of 9-nitro-Luotonin A [7] (among other Luotonin A derivatives) from 3-oxo-1H-pyrrolo[3,4-b]quinoline [8] and a nitroisatoic anhydride building block (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinazolin‐4(3 H )‐ones (aka 4‐oxoquinazolines) are a structural sub‐category that have interesting properties such as antitumor ( e. g ., quinazolinone 1 ), anticonvulsant, and antitubercular behavior . In particular, 2‐cyanoquinazolin‐4(3 H )‐ones are useful synthetic scaffolds for the preparation of derivatives with anti‐inflammatory activity, antitumor derivatives of the natural product Luotonin A, and NMDA receptor antagonists . The synthetic utility of 2‐cyanoquinazolinones is partly owed to the nitrile group, as it can be displaced by nucleophiles such as hydroxide, alkoxides, thiolates and amines or converted to thioamides, tetrazole or amidines by treatment with NaSH, NaN 3 or amines, respectively…”
Section: Introductionmentioning
confidence: 99%
“…2‐Cyanoquinazolinones are typically prepared by dehydration of the respective carboxamides, or oximes, from cyclisation of thiocarbamoyl cyanides with anilines, and from condensation with cyanogen . A more recent method, includes the two‐step preparation of cyanoquinazolinone 4 via dithiazolimine 3 , starting from aniline‐2‐carboxylates and 4,5‐dichloro‐1,2,3‐dithiazolium chloride 2 (aka Appel salt) that acts as an ‘umpolung’ source of cyanomethylene (Scheme ) …”
Section: Introductionmentioning
confidence: 99%